Setting group-based adaptive coordination of overcurrent and distance relays considering changes in grid topology - Hossein Mohammadi; Reza Mohammadi Chabanloo; Mahdi Ghotbi-Maleki (International Journal of Electrical Power & Energy Systems)
Changes in electric network topology, such as line outages, alter fault currents, potentially causing mis-coordination among protective relays. This paper presents an adaptive protection scheme for coordinating overcurrent relays (OCRs) and distance relays (DSRs) using setting groups. The proposed method adjusts group settings in response to line outages, employing a metaheuristic optimization algorithm to cluster possible network topologies into setting groups and determine optimal characteristic curves. Nested within this framework, linear programming algorithm solves a sub-problem to compute optimal time multiplier settings for OCRs. The objective function of the linear programming is designed to prevent the excessive clustering of topologies into a limited number of setting groups, addressing a common limitation of optimization-based clustering. Simulation results indicate that employing comprehensive settings across all network topologies either results in mis-coordination or significantly increases OCR operating times. In contrast, the proposed method achieves complete coordination across all topologies by optimizing characteristic curves, demonstrating superior performance over conventional approaches. Evaluated on the IEEE 8-bus and 30-bus test systems, this approach eliminates mis-coordination and markedly reduces the objective function value compared to existing methods, confirming its effectiveness for adaptive OCR-DSR coordination.